Hitting Two Birds with One Stone: How Russian Countersanctions Intertwined Political and Economic Goals. Issue 2 (April 2020) - Pospieszna, Paulina; Skrzypczyńska, Joanna; Stępień, Beata
ABSTRACT: This article explicates the intertwined economic and political goals behind the imposition of countersanctions through an analysis of their premises and outcomes for Russia's domestic economy. The evidence supports the argument that retaliation was designed to benefit the Russian domestic food industry, reorient trade relations, and bolster domestic public support for this sector while politically penalizing sanctioning countries. An important contribution of this article is to demonstrate how sanctions imposed on nondemocratic target countries, which play an important role in international affairs, is like a tit-for-tat game, which may have additional effects and also unintended political, economic, and social consequences not yet observed.